PHASE-ISOTROPIC CORNER REFLECTOR FOR FIBER-OPTIC CONVERTER - A. S. Nikitin; A. N. Borisov (Известия высших учебных заведений: Проблемы энергетики)
The article is devoted to the design of optical device ‒ phase isotropic corner reflector, which may find application as a mirror in the fiber-optic converter. The use of phase-isotropic elements will reduce the effect of a light signal phase shift on reflection from the mirror mounted on the end of the fiber sensor. The work analyzes the existing phase devices and suggests a device using real film-forming materials, the angle of incidence of radiation, and the materials of the prism.